Diagnostic overview of blood‐based dysferlin protein assay for dysferlinopathies. Issue 3 (16th June 2014) - Ankala, Arunkanth; Nallamilli, Babi R.; Rufibach, Laura E.; Hwang, Esther; Hegde, Madhuri R.
ABSTRACT Introduction: Dysferlin deficiency causes dysferlinopathies. Among peripheral blood mononuclear cells (PBMCs), the dysferlin protein is expressed specifically in CD14+ monocytes. Methods: We quantified dysferlin protein levels in PBMC lysates of 77 individuals suspected clinically of having a dysferlinopathy to screen for true positives. Subsequent molecular confirmation was done by Sanger sequencing and comparative genomic hybridization arrays to establish diagnosis. Results: Of the 44 individuals who had significantly reduced dysferlin levels (≤10%), 41 underwent molecular testing. We identified at least 1 mutation in 85% (35 of 41), and 2 mutations, establishing a dysferlinopathy diagnosis, in 61% (25 of 41) of these individuals. Among those with dysferlin protein levels of >10% (33 of 77), only 1 individual (of 14 who underwent molecular testing) had a detectable mutation. Conclusions: Our results suggest that dysferlin protein levels of ≤10% in PBMCs, are highly indicative of primary dysferlinopathies. However, this assay may not distinguish carriers from those with secondary dysferlin reduction. Muscle Nerve50: 333–339, 2014